The Influence of Electronic Word of Mouth, Trust, and Perceived Value on Consumer Purchase Intentions of Automotive Brand Arvi Creations - Adib Pradipta; Adnan Kasofi; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
This study aims to examine the influence of electronic word of mouth (e-WOM), trust, and perceived value on consumer purchase intention toward the local automotive brand Arvi Creations. The research employs a quantitative approach using a survey method. Data were collected through an online questionnaire distributed to 167 respondents who had obtained information about Arvi Creations from digital media. The sampling technique applied was non-probability sampling, combining purposive and snowball sampling methods. Data analysis was conducted using multiple linear regression to test both partial and simultaneous effects among the variables. The results indicate that e-WOM, trust, and perceived value have a positive and significant effect on purchase intention. Partially, trust is the most dominant variable influencing consumer purchase intention, followed by e-WOM and perceived value. Simultaneously, these three independent variables explain most of the variation in consumer purchase intention. These findings support the relevance of the Theory of Planned Behavior in explaining automotive consumer behavior in the digital era. This study also provides practical implications for local automotive brands in enhancing purchase intention through managing positive e-WOM, building consumer trust, and creating superior product value.